Plunging when drilling: Effect of using blunt drill bits (2012)
Objective: Plunging when drilling can be a detrimental factor in patient care. There is, although, a general lack of information regarding the surgeon's performance in this skill. The aim of this study was to determine the effect that using sharp or blunt instruments had on the drill bit's soft tissue penetration, using a simulator. Materials and Methods: Surgeons taking part in an International Trauma Course were invited to participate. Two groups were defined: experienced and inexperienced surgeons. Twelve holes were drilled in the following order: 3 holes with a sharp drill bit in normal bone (SNB), 3 holes with a sharp drill bit in osteoporotic bone (SOB), 3 holes with a blunt drill bit in normal bone, and 3 holes with a blunt drill bit in osteoporotic bone. Mean values and Student t tests were used for statistical analysis. Results: Thirty-seven surgeons participated, 20 experienced and 17 inexperienced surgeons. Mean plunging depths for SNB, SOB, blunt drill bit in normal bone, and blunt drill bit in osteoporotic bone were, respectively, 5.1, 5.4, 21.1, and 13.9 mm for experienced surgeons and 7.6, 7.7, 22, and 15.9 mm for inexperienced surgeons. Drilling with SNB and with SOB was statistically different, with inexperienced surgeons plunging 2.5 mm (P = 0.31) and 2.6 mm (P = 0.042) deeper, respectively. There was a difference (P less than 0.001) between sharp and blunt drill bits in all drilling conditions for both the groups. Conclusions: Our study showed a significant difference in plunging depth when sharp or bunt drill bit was being used. Surgeons, regardless of their experience level, penetrate over 20 mm in normal bone and over 10 mm in osteoporotic bone. Copyright © 2012 by Lippincott Williams and Wilkins.